DELAYED BREAKING OF GELLED HYDROCARBON FRACTURING FLUID - THOMAS, TODD, R; SMITH, KEVIN, W (1997)
Hydrocarbon fracturing fluids are made by combining organic phosphate esters with polyvalent metal salts in hydrocarbon carriers to form gels; breaking of the gel is retarded or otherwise controlled over a wide range of water concentrations through the use of slowly soluble alkaline earth metal compounds, preferably hard burned magnesium oxide, which may be added along with the gel component. On obtient des liquides de fracturation hydrocarbonés en combinant des esters de phosphate organique et des sels de métaux polyvalents dans des véhicules hydrocarbonés pour former des gels. Il est possible de retarder la rupture du gel, ou bien de la contrôler sur une large gamme de concentrations d'eau, en utilisant pour cela des composés de métaux alcalino-terreux à dissolution lente, de préférence à base d'oxyde de magnésium fort-cuit, que l'on peut ajouter à la composition du gel.